2018
DOI: 10.18203/2319-2003.ijbcp20181649
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of prucalopride in the treatment of chronic constipation

Abstract: Background: Chronic constipation is a common condition that significantly impacts health care utilization, productivity, and quality of life. Laxatives are commonly used, although often insufficient in restoring normal bowel function or providing adequate relief. There remains a significant need for the development of novel agents to optimize treatment of this condition. Prucalopride, a selective, high-affinity 5-hydroxytryptamine 4 receptor agonist, stimulates gastrointestinal and colonic motility and allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…[ 14 22 23 ] Our study had 68% of patients in the ≤65 years age group, which was similar to a study done by Kanaki et al . [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 22 23 ] Our study had 68% of patients in the ≤65 years age group, which was similar to a study done by Kanaki et al . [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events recorded were mostly GI symptoms, mild to moderate in severity within the known pharmacological side effect profile of our study drug. [ 12 14 22 24 ] Headache and diarrhea were mostly reported from the Prucalopride arm with the incidence of nausea, flatulence, and bloating side effects being equal in both groups. Diarrhea was mild, transient, and self-limiting owing to prucalopride's mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms of constipation are abdominal pain, hard stool, etc. at the same time, patients will feel anorectal obstruction, and also often have the feeling of incomplete emptying after defecation, and even need manual operation [1][2] . It has been reported that constipation not only causes troubles in patients' daily life, but also affects patients' emotional health, and then induces a variety of physical diseases [3] .…”
Section: Introductionmentioning
confidence: 99%